The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.pec.2019.03.020
|View full text |Cite
|
Sign up to set email alerts
|

What we know about media communication on antibiotics and antimicrobial resistance: A systematic review of the scientific literature

Abstract: Systematically review the literature regarding media communication about antibiotics and anti-microbial resistance (AMR) to synthesise its key characteristics and impact effectiveness, identifying gaps and areas for further research. Methods: A comprehensive systematic review covering five international databases for articles published between 1 st September 2008 and 1 st September 2018 was performed using the registered protocol (PROSPERO: CRD42018116464). The search using terms related to media communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Existing studies on news media representations of AMR mainly focused on English news media from high-income countries [ 3 8 ] but seldom in less-developed countries such as India, China and South Africa that consumed the largest amount of antibiotics in the world [ 9 11 ]. Despite a growing research interest in the epidemiology of AMR in low- and middle-income countries [ 12 – 14 ], the limited research in media representation of AMR risk in these countries may be due to a general overlook of the importance of media context in shaping public perception, policies and stakeholder engagement regarding the issue of AMR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies on news media representations of AMR mainly focused on English news media from high-income countries [ 3 8 ] but seldom in less-developed countries such as India, China and South Africa that consumed the largest amount of antibiotics in the world [ 9 11 ]. Despite a growing research interest in the epidemiology of AMR in low- and middle-income countries [ 12 – 14 ], the limited research in media representation of AMR risk in these countries may be due to a general overlook of the importance of media context in shaping public perception, policies and stakeholder engagement regarding the issue of AMR.…”
Section: Introductionmentioning
confidence: 99%
“…This may drive primarily technological rather than multidisciplinary approaches to AMR in these countries. Most existing studies analysed news media data on AMR in one single country for a short period [ 8 , 15 ], and mainly analysed printed media despite a global increase in the consumption of online news with the expansion of digital communication technologies [ 6 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twitter is a popular social media microblogging platform that uses short messages (280 characters) and has around 300 million active users per month, with around 500 million tweets per day [1,2]. A recent systematic review of media communication on antibiotics and antimicrobial resistance found that social media (Twitter or Facebook) was a means of health information sharing in 32% of the studies, second only to print media with 53% of the studies [3]. Tweet chats are real-time discussions among Twitter users where a moderator posts questions during a preestablished duration of time and people respond to tweets using a unique hashtag.…”
Section: Introductionmentioning
confidence: 99%
“…The global spread of AMR may compromise our ability to treat existing and emerging common infectious diseases, as well as undermine many other improvements in health and sustainable development [2]. "Overuse" and "suboptimal use" of antimicrobials, including antibiotics in humans, farmed animals and the environment, mobility of human populations between regions and healthcare facilities, poor infection control, inadequate sanitary conditions and inappropriate food-handling are considered the main factors leading to the emergence and spread of AMR [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%